Evaluating criteria of research activity: damages to the system of scientific communication in Spanish - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2015)
Some negative consequences of the criteria for evaluating research production of Spanish scholars are described. The prevalence of the Journal citation reports impact factor is harmful for the scientific publications of Spanish publishers, limits the open access policies of university publishers and university libraries, and excludes research activities of numerous areas of social sciences and humanities.
Keywords: Research evaluation; Cneai; Fecyt; Open access; OA; Spain; Academic publishers; University presses.